Swallowing dysfunction in healthy older people using pharyngeal pressure‐flow analysis. Issue 1 (9th September 2013) - Omari, T. I.; Kritas, S.; Cock, C.; Besanko, L.; Burgstad, C.; Thompson, A.; Rommel, N.; Heddle, R.; Fraser, R. J. L.
Abstract Background Age‐related loss of swallowing efficiency may occur for multiple reasons. Objective assessment of individual dysfunctions is difficult and may not clearly differentiate these from normal. Pharyngeal pressure‐flow analysis is a novel technique that allows quantification of swallow dysfunction predisposing to aspiration risk based on a swallow risk index (SRI). In this study, we examined the effect of ageing on swallow function. Methods Studies were performed in 68 healthy subjects aged 20–91 years (mean 59 years; 29 male), asymptomatic for oropharyngeal disease. Swallowing of liquid and viscous boluses was recorded with a pressure‐impedance catheter. Indices of swallow function including the SRI, postswallow residues, upper esophageal sphincter opening and bolus transit time were derived using purpose designed software. Key Results Swallow function worsened with increasing age with a significant decline after 80 years. Higher SRI correlated with increasing age (r = 0.257, p < 0.05 for liquids and r = 0.361, p < 0.005 viscous bolus). Subjects over 80 years were overrepresented amongst those with an SRI considered diagnostically relevant (SRI > 15). In addition, upper esophageal sphincter opening was reduced and postswallow residues increased in older subjects. Conclusions & Inferences Pharyngeal pressure‐flow analysis reveals multiple functional abnormalities in older individuals. The higher SRI levels seen in asymptomatic elders possibly reflect a loss of functional reserve with ageing. Automated impedance manometry analysis of swallow function may allow the risk of developing disordered swallowing to be quantified numerically.